Preclinical pharmacology of alogabat: a novel GABAA-α5 positive allosteric modulator targeting neurodevelopmental disorders with impaired GABAA signaling - Cecere, Giuseppe; Ballard, Theresa M.; Knoflach, Frederic; Honer, Michael; Hipp, Joerg F.; Garces, Pilar; Mueggler, Thomas; Künnecke, Basil; Bruns, Andreas; Prinssen, Eric P.; Schoenenberger, Philipp; Janz, Philipp; et al. (Frontiers in Pharmacology, 2025)
BackgroundAlterations in the GABAergic system contribute to the pathophysiology of neurodevelopmental disorders, including autism spectrum disorder (ASD) and Angelman syndrome (AS), particularly in cases involving large deletions in the 15q11–13 region. Positive modulation of GABAA-α5 receptors may provide a novel therapeutic approach without the typical side effects associated with non-selective GABAA positive allosteric modulators such as diazepam.MethodsAlogabat was assessed for binding and functional activity at GABAA-α5β3γ2 receptors in vitro and in electrophysiological studies using hippocampal slices. In vivo studies in rodents included receptor occupancy (RO) using a selective GABAA-α5 tracer (autoradiography), pharmacological MRI, and electroencephalography (EEG). Alogabat was evaluated for its effects on the repetitive behavior phenotype in BTBR and contactin-associated protein-like 2 (Cntnap2−/−) knockout mice, seizure models, cognitive performance in rats, and rotarod performance following combination treatment with diazepam.ResultsAlogabat is a potent positive allosteric modulator of GABAA-α5 receptors, with binding and functional selectivity. Receptor occupancy studies provided direct proof of dose-dependent target engagement. Functional circuit modulation was demonstrated by dose-dependent regional perfusion changes in pharmacological MRI and changes in EEG theta- and beta-band power in rats. At >50% GABAA-α5 receptor occupancy, alogabat normalized elevated self-grooming behavior in both Cntnap2−/− and BTBR mice and exhibited antiepileptic activity in rats. Alogabat did not impair cognition in wildtype rats at GABAA-α5 receptor occupancy up to 75%, although impairment occurred at higher doses, probably due to increased activity at other receptor subtypes and/or saturation of α5 receptors. Alogabat did not worsen diazepam-induced impairment on the rotarod test.ConclusionAlogabat showed beneficial effects in mouse models relevant to neurodevelopmental disorders and anti-seizure activity at doses that did not produce cognitive, sedative, or motoric side effects.